A 'work in progress'?: UK researchers and participation in public engagement. (1st January 2017) - Burchell, Kevin; Sheppard, Chloe; Chambers, Jenni
Abstract : The funders of UK research seek to embed public engagement by researchers within the culture of UK research. Within this context, this paper provides a snapshot of the UK public engagement landscape by reporting on new quantitative research that examines the experiences and perspectives of UK researchers (n = 2, 454) and public engagement support staff (n = 260). The research suggests that ambitions to embed public engagement by researchers within institutional cultures can be understood as a 'work in progress'. There are indications that public engagement is part of the UK research landscape. At the same time, the research suggests that researchers' public engagement efforts are currently constrained; there is evidence of a disconnect between researchers themselves and broader institutional contexts of public engagement, and the sector is overwhelmingly driven by funding and rewards for research, teaching and other activities. In conclusion, these results indicate that, while current strategies have been helpful, longer term effort is required, perhaps targeting particular domains and, more fundamentally, perhaps featuring greater support and reward for public engagement.